Optimization Techniques for Resource Allocation in Cloud Computing Systems - Kumain, Kiran (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The distribution of available resources is an essential aspect of cloud computing systems. It entails allocating computer resources to various programmes and users in order to guarantee that the available resources are utilized in an efficient, effective, and equitable manner. The optimization of resource allocation in cloud computing systems presents a number of challenges, such as heterogeneity, multi-objective optimization, large-scale optimization, dynamic optimization, and user satisfaction. Other challenges include privacy and security, large-scale optimization, and dynamic optimization. Researchers have made tremendous progress in designing algorithms, models, and frameworks to address these concerns despite the difficulties they face in doing so. In this overview of the relevant literature, we focus on research that investigates methods for resource allocation and optimization in cloud computing systems. We provide a brief synopsis of the most important findings from these studies and provide them in table form, drawing attention to the study methodologies, algorithms, and optimization strategies that were applied. In addition, we address potential future research areas and outline the obstacles that researchers encounter when attempting to optimize the allocation of resources in cloud computing systems. The purpose of this literature review is to offer a complete overview of the current state of research in resource allocation and optimization in cloud computing systems, and it may also serve as a valuable reference for researchers and practitioners working in this subject.